Analiza przestrzeni ekologicznej i społecznej dla elektrowni wiatrowych na przykładzie powiatu gryfińskiego = Analysis of the area of environmental and social for wind power plants on the example of Gryfino district - Słobodzian-Ksenicz, Oryna; Jasiewicz, Marzena; Kolenda, Paulina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study included an analysis of environmental and social space for wind farms in the Gryfino district example. Characterized wind conditions, environmental constraints and social conditions for existing and planned investments. The presence of parks and Natura 2000 site does not interfere with existing and planned wind farms. The results of the survey among the population of the county show a lack of information to the local community.
Keywords: elektrownia wiatrowa; lokalizacja; wiatr; środowisko; wind turbine; location; wind; environment